Dynamic changes in sumoylation related proteins SUMO1, SENP1, and UBC9 during the peri implantation period in mice - Ezgi Golal; Cemre Nur Balci; Nuray Acar (Scientific Reports)
Abstract The healthy progression and termination of pregnancy depend critically upon embryo development, acquisition of uterine receptivity, implantation, and decidualization during the peri-implantation period. Sumoylation is a post-translational modification that affects the stability, transcriptional activity, and cellular localization of proteins. In our study, we investigated the localization and expression of SUMO1 (small ubiquitin-like modifier), SENP1 (sentrin-specific protease 1), and UBC9 (SUMO-conjugated enzyme UBC9), members of the sumoylation mechanism, in the mouse uterus and implantation sites during the peri-implantation period. Localization and expressions of SUMO1, SENP1, and UBC9 were determined by immunohistochemistry and Western blot, respectively. Estrogen (E2) and progesterone (P4) levels were measured by ELISA. SUMO1 was at the highest level in the luminal and gland epithelium and stroma on the 5th day of pregnancy compared to other pregnancy days. SENP1 was high on the 4th but low on the 5th day of pregnancy. On the 6th and 8th days of pregnancy, expressions of SUMO1 and SENP1 were decreased, while the amount of UBC9 was similar to other days of pregnancy. According to ELISA, E2 reached its highest level on the 4th day of pregnancy, and P4 reached its highest level on the 8th day of pregnancy. SUMO1, SENP1, and UBC9 are expressed at different levels in the uterus and implantation sites during early pregnancy. Our findings suggest that the sumoylation mechanism may play a role in the implantation and decidualization processes of mice.